2012
DOI: 10.1080/03079457.2012.712673
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the effects of aflatoxin B1givenin ovoon the proximal tibial growth plate of broiler chickens: histological, histometric and immunohistochemical findings

Abstract: Detrimental effects of aflatoxin B 1 (AFB 1 ) on the embryonic development of broiler tibia and its proximal growth plate were determined by means of histological, histometric and immunohistochemical methods. For this, 420 fertile eggs from parent stocks of Ross 308 broiler chickens were divided into five groups according to the proposed treatment: a control untreated group, a group injected with 30% ethanol and three further groups to be injected with 5 , 15 or 40 ng AFB 1 . The eggs were injected into the ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 45 publications
0
20
1
Order By: Relevance
“…Embryonic AFB1 exposure can lead to morphological defects [212], such as abnormal area opaca cells [210,214], skeletal defects in the tibia growth plate [213], and inhibition of bursal follicle development [210,214]. These mutagenic effects can reduce embryo viability and adversely affect hatched progeny.…”
Section: Embryotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Embryonic AFB1 exposure can lead to morphological defects [212], such as abnormal area opaca cells [210,214], skeletal defects in the tibia growth plate [213], and inhibition of bursal follicle development [210,214]. These mutagenic effects can reduce embryo viability and adversely affect hatched progeny.…”
Section: Embryotoxicitymentioning
confidence: 99%
“…In experimental settings, in ovo exposure of chickens or turkeys to AFB1 caused DNA damage in the embryonic liver and increased embryo mortality [131,161,[210][211][212][213][214][215]. When introduced into the maternal diet to simulate the natural route of embryonic exposure, AFB1 caused reduced hatchability [130,131,161].…”
Section: Embryotoxicitymentioning
confidence: 99%
“…The toxic effects of aflatoxin in poultry have been thoroughly studied by determining their teratogenic, carcinogenic, mutagenic, and growth inhibitory effects (26). The biochemical, haematological (4,22), immunological (17), and pathological (24) effects of aflatoxin have also been described in details.…”
Section: Introductionmentioning
confidence: 99%
“…Zeolites (12,16), bentonites (7,11,26), and yeast/esterified glucomannan (1,4,6,15) were opted for because of their effect on reducing aflatoxin absorption from the gastrointestinal tract. Some studies have showed that the best method for decontamination is biological degradation by yeast and yeast components, which can remove aflatoxin under mild conditions, without using harmful chemicals or causing noticeable losses in nutritive value and palatableness of the feed (21,30).…”
Section: Introductionmentioning
confidence: 99%
“…The most common are weakness, anorexia with reduced growth rate, poor feed utilization, slow weight gain, decreased egg weight and production, and increased mortality (Oguz et al, 2000). The toxicity of aflatoxin in poultry has been extensively studied to determine their teratogenic, carcinogenic, mutagenic, and growth-inhibition effects (Oznurlu et al, 2012). The biochemical, hematological Azizpour et al, 2012), immunological (Mogadam & Azizpour, 2011), and pathological (Ortatatli & Oguz, 2001) effects of aflatoxins have also been described in depth.…”
Section: Introductionmentioning
confidence: 99%